THE IDENTITY CONSTRUCTION OF NEWCOMER TEACHERS IN ENGLISH EDUCATION THROUGH REFLECTIVE WRITING - Yuliyana Yuliyana (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
ABSTRACT This study explores teacher identity among four newcomer teachers who are taking their master degree in English education. Specifically, it engages a holistic perspective to research the connection between personal and professional life experiences that shaped their teacher identity. This study tries to look into to what extent the teacher identity is constructed during English education master program. The researcher gathered reflection writing from the participants about their life stories, journey, and their motivation of continuing study. Their institution and formal courses are not the only aspect that could construct their identity. Work experiences and others’ sharing stories also give the big influence on their teacher identity. Keywords: teacher identity; reflective writing; newcomer teacher